2014
DOI: 10.1016/j.jep.2014.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Cecropia pachystachya extract attenuated the renal lesion in 5/6 nephrectomized rats by reducing inflammation and renal arginase activity

Abstract: These results suggest that the reduction of renal arginase activity, p-JNK and TGF-β expression can explain the mechanism by which the treatment with C. pachystachya reduced the inflammation and improved renal function. This study presents the potential use of Cecropia pachystachya in the treatment of chronic renal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
3
8
0
1
Order By: Relevance
“…However, pretreatment with both rhizomes prevented the increase of arginase activity in hypertensive rats. Previous studies have reported up-regulation of arginase activity and decreased NO in hypertension (Bagnost et al, 2008(Bagnost et al, , 2010Maquiaveli et al, 2014). This result is in agreement with recent studies that inhibition of arginase activity is crucial for the management of hypertension (Bagnost et al, 2008(Bagnost et al, , 2010Maquiaveli et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, pretreatment with both rhizomes prevented the increase of arginase activity in hypertensive rats. Previous studies have reported up-regulation of arginase activity and decreased NO in hypertension (Bagnost et al, 2008(Bagnost et al, , 2010Maquiaveli et al, 2014). This result is in agreement with recent studies that inhibition of arginase activity is crucial for the management of hypertension (Bagnost et al, 2008(Bagnost et al, , 2010Maquiaveli et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported up-regulation of arginase activity and decreased NO in hypertension (Bagnost et al, 2008(Bagnost et al, , 2010Maquiaveli et al, 2014). This result is in agreement with recent studies that inhibition of arginase activity is crucial for the management of hypertension (Bagnost et al, 2008(Bagnost et al, , 2010Maquiaveli et al, 2014). However, several authors have reported dietary plant phenolics exhibited inhibitory effect on arginase activity (Kim et al, 2013;Manjolin, dos Reis, Maquiaveli, Santos-Filho, & Da Silva, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…It is also used as a diuretic (Rocha et al 2007). Pharmacological activities were reported in extant studies including the development of anxiolytic, antidepressant (Velá zquez et al, 2003;Consolini et al, 2006;Gazal et al, 2014;Ortmann et al, 2016), hypoglycemic (Aragã o et al, 2010), antioxidant (Consolini et al, 2006;Farias et al, 2013;Souza et al, 2014;, cardiotonic (Consolini & Migliori, 2005;Gazal et al, 2014), sedative (Hikawczuk et al, 1998), anti-inflammatory (Pacheco et al, 2014;Maquiaveli et al, 2014), antimicrobial (Souza et al, 2014), and leishmanicidal (Cruz et al, 2013) properties for aqueous and alcoholic extracts prepared by infusion or maceration of C. pachystachya leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorogenic acid and orientin were the main compounds identified in AE and EtE of leaves, which have been previously shown to have an anti-inflammatory effect (Maquiaveli et al. 2014 ).…”
Section: Biological Activities and Chemical Compounds Reported In Thementioning
confidence: 94%